(untitled) (Indian Journal of Child Health, 2018)
Background: Bacterial meningitis is a significant life-threatening illness during infancy and childhood. Delay in distinguishing bacterial from viral or other aseptic meningoencephalitis may have irrevocable consequences. A typical case of pyogenic meningitis without prior antibiotics may not create any diagnostic problems, but prior treatment with inappropriate and inadequate antibiotics may cause sufficient alteration in biochemistry and cytology of cerebrospinal fluid (CSF), and organisms may not get isolated from blood or CSF culture. Objective: C-reactive protein in CSF (CSF-CRP) has been reported to be one of the most reliable and early indices to differentiate bacterial from non-bacterial meningitis. This study was undertaken to evaluate the diagnostic significance of CSF- CRP as an early indicator in the differentiation of bacterial from non-bacterial meningitis. Materials and Methods: This descriptive study was done in children in the age group of 1 month to 12 years who were admitted with history and clinical features suggestive of acute central nervous system infection. CSF was analyzed for macroscopic appearance, pleocytosis, proteins, and sugar content, Grams and Ziehl